Real-time intrapartum fetal electrocardiogram analysis - Crittenden, Mark E. (1997)
The research within this thesis concerns the monitoring of the fetus during labour, using the fetal electrocardiogram (FECG). A versatile FECG analysis system was developed for the Microsoft Windows environment, to allow various FECG parameters to be extracted. Algorithms, currently used in other FECG analysis systems, were implemented using Object Oriented Programming, thus allowing new algorithms to be easily added at a later stage. Although these current algorithms have been demonstrated by several authors, it was felt that they had been used with only partial investigation of their limitations, and with failure to fully determine their accuracy in controlled conditions. These factors are fully addressed within this thesis. By developing a FECG simulator, in which heart-rate, morphology, and noise levels could be varied, the ability of the analysis algorithms to extract the parameters, and the accuracy of these parameters under different noise conditions, were thoroughly checked. Both ability and accuracy were shown to be very good in ideal noiseless conditions; but, with the addition of noise, there exists a compromise between parameter accuracy when the morphology is static, and parameter accuracy when the morphology is changing.